Reference Intervals for Selected Hematology and Clinical Chemistry Measurands in Temminck's Pangolin (Smutsia temminckii) - Hooijberg, Emma H.; Lourens, Karin; Meyer, Leith C. R. (Frontiers in Veterinary Science, 2021)
Pangolins are the world’s most trafficked non-human mammals. A significant number of Temminck’s pangolins (Smutsia temminckii) are presented for veterinary care and rehabilitation in southern Africa. Little is known about the physiology and normal health of this species, making diagnosis and medical management difficult. This study aimed to establish reference intervals (RIs) for hematology and plasma clinical chemistry in the Temminck’s pangolin. RIs were generated according to international guidelines using samples from 27 healthy free-living (18) and rehabilitated (9) pangolins. Hematology was performed using the Abaxis VetScan HM5 analyzer with manual differentials; clinical chemistry was performed using heparin plasma on the Abaxis VetScan VS2 and Cobas Integra 400 Plus analyzers. Hematology RIs were: RBC 3.88–8.31 x1012/L, HGB 73–150 g/L, HCT 26–51%, MCV 59–72 fL, MCH 15.6–21.4 pg, MCHC 257–325 g/L, RDW 14.3–19.1%, WBC 1.80–10.71 x109/L. Vetscan VS2 clinical chemistry RIs were: albumin 27–41 g/L, ALP 26–100 U/L, ALT 25–307 U/L, amylase 267–826 U/L, bilirubin 4–10 mol/L, calcium 2.1–2.2 mmol/L, globulin 21–55 g/L, glucose 3.8–10.0 mmol/L, phosphate 1.3–2.6 mmol/L, potassium 3.6–5.9 mmol/L, sodium 132–140 mmol/L total protein 52–84 g/L, and urea 5.3–11.4 mmol/L. RIs for creatinine were not calculated as analytical imprecision exceeded analytical performance goals. Cobas Integra clinical chemistry RIs were: albumin 22–33 g/L, ALP 20–104 U/L, ALT 17–291 U/L, amylase 466–1533 U/L, bilirubin 1–14 mol/L, calcium 2.0–2.4 mmol/L, creatinine <58 mol/L, globulin 23–49 g/L, glucose 3.6–10.1 mmol/L, phosphate 1.0–2.2 mmol/L, potassium 3.1–5.8 mmol/L, sodium 137–150 mmol/L, total protein 47–72 g/L, and urea 6.0–12.5 mmol/L. There was significant bias between the two chemistry analyzers for several measurands. Differences were found for some analytes between free-living and rehabilitated animals, probably reflecting differences in nutrition and hydration. These are the first RIs generated for Temminck’s pangolin. These results will allow veterinarians to better determine pangolin health status, formulate optimal treatment plans and increase patient survival rates in this endangered species.